Study on the integration model of port clearance in food supervision in the Guangdong Hong Kong Macao Greater Bay Area - ZHANG Yiming (Shipin yu jixie, 2023)
At present, the integration construction of the Guangdong Hong Kong Macao Greater Bay Area is deepening. Among them, the port customs integration model in food supervision in the Guangdong Hong Kong Macao Greater Bay Area has problems such as inconsistent regulatory standards, cumbersome customs clearance procedures, and information asymmetry, which have led to increasingly prominent issues of low food supervision efficiency. In this regard, effective innovation in the integration model of port clearance can be promoted by unifying the food safety supervision standards of Guangdong, Hong Kong, and Macao, constructing an integrated port clearance procedure mechanism, and strengthening information sharing and collaborative supervision. At the same time, in order to strengthen the supporting construction of improving the efficiency of food supervision in the Guangdong Hong Kong Macao Greater Bay Area, it is still necessary to further improve the level of port services in practice, and provide more convenient one-stop services for food customs clearance.